A quantitative gain‐independent assessment of the left atrial appendage as a method of thromboembolic risk stratification. Issue 2 (30th December 2021) - Slostad, Brody; Lee, Kevin; Trybula, Michael; Konda, Sreenivas; Macrinici, Victor; Frazin, Leon; Kansal, Mayank
Abstract: Background: Visual assessment of the left atrial appendage (LAA) by echocardiography for the presence of thrombus is inherently qualitative. However, whether quantitative assessments can provide increased value over qualitative assessment has not been thoroughly examined. Methods: One hundred and thirty‐eight patients (mean age 59 ± 13 years, 70% male) undergoing transesophageal echocardiography prior to pulmonary vein isolation or electrical cardioversion were retrospectively studied. LAA were examined by two expert readers and identified as thrombus, sludge, spontaneous echocardiograph contrast, or normal. LAA were then separately examined to calculate a gain‐independent ratio between the average pixel density of the LAA cavity and that of the LAA wall (C/W ratio). Results: C/W ratio was significantly related with qualitative LAA analysis ( p  < 0.0001) and with thromboembolic events (OR 1.60, 95% CI 1.095–2.347, p  = 0.02). The C/W ratio (AUC 0.73, 95% CI 0.60–0.86) was a reliable predictor for future thromboembolic events when compared to expert reader LAA assessment (Expert Reader 1 AUC = 0.72, 95% CI 0.53–0.90; Expert Reader 2 AUC = 0.69). Conclusions: The C/W ratio may be a complementary method to adjudicate thromboembolic risk in patients with AF that is readily quantifiable at time of TEE. Abstract : This study demonstrates that our novel 2D TEE method (the C/W ratio) is a simple, gain‐independent measurement that is significantly related to expert reader LAA analysis and predicts thromboembolic events in patients with atrial fibrillation. Our study suggests that the C/W ratio may be a complementary method to adjudicate thromboembolic risk in patients with AF that is readily quantifiable at time of TEE and may be useful in cases of uncertain qualitative assessment.